Determinants of CO2 emissions: evidence from Asia and the Pacific region - Jalil, Siti Ayu; Habibullah, Muzafar Shah; Ismail, Normaz Wana; Mohd Noor, Zaleha (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
Asia and the Pacific region cover the countries situated in East Asia, South Asia and the Pacific islands are the fastest growing economic region and the source of global greenhouse gas emissions. It is understood the dilemma facing by the governments across this region their need to balance between boosting economic growth to eradicate poverty while simultaneously controlling the increased in carbon emissions. This study attempts to investigate the factors contributing to the high growth of per capita CO2 emissions within 32 countries in this region for the period of 1971-2009. It is indeed crucial to search for the roots of the problem before embarking any policy instruments. Employing the GMM estimations method to investigate the eight socioeconomic determinants of CO2 emissions in the context of a panel framework would help to control for individual heterogeneity and consequently remove the risks of biased results. Out of the eight factors, GDP per capita, energy usage and energy consumption from fossil fuel have proven to be the crucial factors though FDI and agriculture production do have a significant impact on per capita CO2 emissions. However urbanization, industrial production and education show insignificant results.